KEAKURATAN SKRINING FOTO TORAKS DIBANDINGKAN DENGAN SKRINING GEJALA DALAM MENDETEKSI KASUS TUBERKULOSIS SECARA AKTIF PADA NARAPIDANA DI LEMBAGA PEMASYARAKATAN: SYSTEMATIC REVIEW - Monica She Queen (2021)
Tuberculosis is an infectious disease that is transmitted through droplet nuclei and usually infects the lungs. The process of transmission is very easy to occur, especially in dense and vulnerable populations such as prisoners in prisons, thus a method is needed to actively detect tuberculosis cases so that it can facilitate the control of tuberculosis cases. Some literature suggests a screening method for active case finding of tuberculosis. The most widely used screening for active detection of tuberculosis is chest X-ray screening and symptom screening. This study aims to determine the accuracy of X-ray screening compared to symptom screening in active case detection of tuberculosis towards prisoners in prisons. Method: Systematic review of journals from the online databases of PubMed, Elsevier, and Science Direct. The journals used are journals that discuss screening, tuberculosis, chest X-rays, and prisoners. Result: There are 5 studies which explain that chest X-ray screening has more active case detection of tuberculosis confirmed as having active tuberculosis compared to symptom screening. Conclusion: active case detection of tuberculosis towards prisoners in prison using the chest X-ray screening has a higher degree of accuracy when compared to using symptom screening.